Multi-Objective Decision Making for Z Coordinator and Overcut in µ - EDM process using Tungsten Carbide Electrode for machining of Titanium Alloy - Phan Huu Nguyen (Journal of Machine Engineering)
Research on optimization of technological parameters in micro-EDM is very important, and especially results in multi-objective optimization problem. It led to improve machining performance like machining accuracy, reduced electrode wear and improved surface quality. Recent studies mainly refer to the quality indicators of machining productivity and electrode wear, besides that machining accuracy and surface quality are also very important indicators but published results about them is very limited. In this study, Z Co-Ordinate (Z) and overcut (OC) in micro-EDM using tungsten carbide (WC) electrode for Ti-6Al-4V were decided simultaneously by TOPSIS. Technological parameters which include Voltage (V), Capacitance (C) and Response surface methodology (RPM) were investigated in the presented research work. The results showed that the quality parameters Z and OC at optimal conditions were significantly improved. The surface quality behind the micro-EDM is also analyzed and evaluated, and it is good.